2011
DOI: 10.1039/c1cc14819b
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin and metallothionein: dangerous liaisons

Abstract: Ferritin (Ft) interaction with the Zn-complexes of mammalian MT1, MT2 and MT3 metallothioneins (MT) leads to simultaneous Fe(II) and Zn(II) release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…MTs are small (6–10 kDa), cysteine-rich (33%) metalloproteins that catalyze redox reactions and contain metal binding sites. Although they are mainly involved in the homeostasis of physiological Zn 2+ , they still exhibit the capacity to bind iron because they are thiolate-rich biomolecules33. Considering that the expression of Mt1a and Mt2A was significantly increased in the Fe-Gly group, we speculate that a much larger amount of iron was indeed absorbed into the intestinal epithelia of the rats in this group.…”
Section: Discussionmentioning
confidence: 78%
“…MTs are small (6–10 kDa), cysteine-rich (33%) metalloproteins that catalyze redox reactions and contain metal binding sites. Although they are mainly involved in the homeostasis of physiological Zn 2+ , they still exhibit the capacity to bind iron because they are thiolate-rich biomolecules33. Considering that the expression of Mt1a and Mt2A was significantly increased in the Fe-Gly group, we speculate that a much larger amount of iron was indeed absorbed into the intestinal epithelia of the rats in this group.…”
Section: Discussionmentioning
confidence: 78%
“…Likewise, a combination of computational modeling methods allowed showing how flavin molecules bind to the ferritin protein surface and transfer electrons across the protein shell reaching the iron core [82]. We also recently demonstrated that some metallothioneins can promote iron release from ferritin by pumping electrons through the shell that reduce iron(III) to iron(II), which diffuses into the intracellular milieu [42].…”
Section: Fig 5 Schematic Representation Of the Two Main Mechanisms mentioning
confidence: 99%
“…Otherwise, some metalloproteins such as ceruloplasmin [41] or metallothioneins [42] are capable to respectively promote the uptake or the removal of iron from ferritin, the latter giving rise not only to the existence to free toxic iron(II) but also to putatively damaging free copper(I) or zinc(II) ions that were initially bound to it. Other biomolecules such as glutathione (GSH), xanthine oxidase and superoxide dismutase (SOD) have also been reported to interact with ferritin (cf.…”
Section: Fig 1 Horse Spleen Ferritin Structure: a 24-subunit Oligommentioning
confidence: 99%
“…If, according to the present results and those of Hagen and coworkers, [10] the Fe III ions produced at the Ft ferroxidase centers are available for complexation by a large molecule such as transferrin, it should also be able to act as an oxidant against metallothioneins (MTs). [12] This possibility takes special relevance in view of the Fenton reactivity of Cu I/II ions and the widely assumed presence of copper-containing MTs in brain cells. Bearing this in mind, we studied the iron reconstitution of the two different ferritins from our study (i.e., HuFtH and HsFt) in the presence of the copper-loaded forms of two mammalian MT isoforms (i.e., MT2 and MT3).…”
Section: Resultsmentioning
confidence: 99%
“…However, if this imbalance in L-and H-subunit synthesis leads to the synthesis of pure H apoferritins, and therefore to some events analogous to those we have described here in which the high ferroxidase activity and low Fe [12] provided that the correct combination of isoforms is preserved, otherwise metal-related neuronal disorders could be triggered if parting from this ideal combination.…”
mentioning
confidence: 79%